2013
DOI: 10.1186/1472-6963-13-s1-s6
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of joint commissioning: three discourses of prevention, empowerment and efficiency

Abstract: BackgroundIn recent years joint commissioning has assumed an important place in the policy and practice of English health and social care. Yet, despite much being claimed for this way of working there is a lack of evidence to demonstrate the outcomes of joint commissioning. This paper examines the types of impacts that have been claimed for joint commissioning within the literature.MethodThe paper reviews the extant literature concerning joint commissioning employing an interpretive schema to examine the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 47 publications
0
27
1
Order By: Relevance
“…Lead commissioning with aligned incentives‘Reinvestment payments’ to providers based on quality of care and reduced costs of emergency care1 scheme North West London Integrated Care Pilot (England)

Note : PACE, Program of All-Inclusive Care for the Elderly; PRISMA, Programme of Research to Integrate Services for the Maintenance of Autonomy; POPP, Partnerships for Older People Projects.

a

Some schemes used more than one financial integration mechanism.

Typology adapted from: Audit Commission (2009), 19 Carson (2010), 20 Department of Health (2013), 5 Dickinson (2013). 21

…”
Section: Resultsmentioning
confidence: 99%
“…Lead commissioning with aligned incentives‘Reinvestment payments’ to providers based on quality of care and reduced costs of emergency care1 scheme North West London Integrated Care Pilot (England)

Note : PACE, Program of All-Inclusive Care for the Elderly; PRISMA, Programme of Research to Integrate Services for the Maintenance of Autonomy; POPP, Partnerships for Older People Projects.

a

Some schemes used more than one financial integration mechanism.

Typology adapted from: Audit Commission (2009), 19 Carson (2010), 20 Department of Health (2013), 5 Dickinson (2013). 21

…”
Section: Resultsmentioning
confidence: 99%
“…Worth over £20M with [40][41][42][43][44][45][46][47][48][49][50] Swallow staff involved, this contract was one of the largest ever negotiated between commercial providers and NHS commissioners. With the contract covering an entire region, the aim was to deploy the suite of software tools to the analytics units of local commissioning organisations, train NHS analysts in using the tools and supply 'wrap around' support from consultants with commissioning expertise to help commissioners translate output from the tools into commissioning decisions.…”
Section: Recruitment and Data Collection Via The First Commercial Promentioning
confidence: 99%
“…it's two silos with a lot of aggro', which was mirrored from government level to the local system (Percy, former PCT chief executive officer and Department of Health senior manager, now freelance consultant). Moreover, a recent study found that despite widespread perceptions of the benefits for patients, there was limited evidence that joint commissioning improved outcomes, 41 although a former King's Fund fellow argued that such evidence was difficult to generate, partly because other initiatives might also have had an impact on outcomes. 42 …”
Section: Definitions and Challengesmentioning
confidence: 99%
“…Three decades after the need for better integration of health and social care was recognized, policymakers are still grappling with what joint commissioning means in principle, and there is even greater uncertainty about what it means in practice (Dickinson et al 2013).…”
Section: Joint Commissioningmentioning
confidence: 99%